Iowa RBA, May 31, 1999 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1999)
Email for the Iowa RBA for May 31, 1999. Highlights include Clark's Grebe, Western Grebe, Little Blue Heron, and Red-necked Phalarope. Includes notes for updates for June 3, and June 4. Epson - sheet feed/flatbed